Analisis Kelayakan Usaha Produksi Tahu di Desa Sumbermulyo Kecamatan Jogoroto Kabupaten Jombang - Laili Indah Trisnawati; Joko Priyono (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to find out whether the tofu business in Sumbermulyo Village, Jogoroto District, Jombang Regency is feasible. This research used descriptive research involving 6 informants as research subjects. Evaluation of business feasibility is carried out by calculating B/C, R/C, ROI, and BEP. The calculation results show that the B/C Ratio has a maximum value of 0.30 and the lowest value is 0.16. The R/C Ratio has a value greater than 1 reaching a maximum of 1.30 and a minimum of 1.16. ROI> 0%, with the highest figure being 8.27% and the lowest being 1.50%, and the BEP unit producing the highest value of 386 and the lowest value of 159, and the BEP rupiah having the highest value of IDR 964,163 and the lowest value of IDR. 674,356.